Grazing management systems: creep grazing for suckling goat kids - Yiakoulaki M.D.; Goetsch A.L.; Sahlu T. (Nutritional and foraging ecology of sheep and goats, 2009)
Creep grazing is a management system designed to match particular pasture forages and (or) grazing areas with specific nutritional requirements of different classes of grazing animals. It allows access of young nursing animals to forage of high quality and palatability (creep area) while excluding mature animals. The young animals through special openings (creep gates) are able to graze the creep area and return for suckling, thus possibly increasing weight gain and weaning weight without concentrate supplementation. In this paper, creep grazing by goats is described, with special attention given to considerations of the location of the creep area, creep gates and forage species. Kids' foraging behaviour and relevant management practices, with highlighting of areas deserved of future research attention, were also discussed.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)